Language Style of Advertisements - Yustiari, Ni Wayan Wida; Rajeg, I Made; Asty Pratiwi, Putu Ayu Senja (e-Journal of Linguistics; Vol 17 No 1 (2023): ejl-JanuaryDO - 10.24843/e-jl.2023.v17.i01.p08, 2022)
The article aims to find the type of language style and the meanings implied in the advertisement. The data were taken from advertisements in Now! Bali magazine was published from May 2018 to June 2018. They were analyzed using the descriptive qualitative method and the theory type of language style (Wells, 2009) and the theory of meaning (Keraf, 2006). The result show that there are seven types of language style applied in them including similes, personification, metonymy, alliteration, assonance, ellipsis, and hyperbole. In terms of meaning, denotative and connotative meanings are implied.